Temporal dynamics and functional annotation of transcriptome rhythmicity in HEK293T cells - Yuling Sun; Huiyu Dong; Fei Ge; Ying Zhao; Shuhan Yang; Yidong Ding; Min Dong; Liming Wang; Tao Zhang (PLoS ONE, 2026)
The endogenous circadian clock drives rhythmic processes in nearly all human cells; however, the temporal organization of the transcriptome in HEK293T cells, a widely used cell line, remains incompletely defined. We synchronized HEK293T cells and performed RNA sequencing at thirteen time points across a 48-hour cycle to map their transcriptome dynamics. Across the time course, principal component analysis revealed clear time point dependent separation of the global transcriptomes; however, coefficient of variation analyses indicated substantially increased divergence among biological replicates starting at T28. In addition, canonical core clock genes showed no detectable circadian rhythmicity when the analysis window extended beyond 28 hours. Genome-wide, only 785 expressed genes displayed rhythmic expression. These rhythmic genes were enriched for cytoplasmic and nuclear compartments, cytoskeletal and membrane related structures, and molecular functions including GTPase activator activity and metal ion binding. Further analysis of expression patterns among arrhythmic genes revealed that only 645 arrhythmic genes displayed time-dependent expression; notably, these genes were enriched in biologically important pathways, including G alpha signaling and structural constituents of chromatin. Together, these results indicate that HEK293T cells exhibit weak intrinsic circadian transcriptome rhythmicity, with most transcripts remaining time independent across the sampled window. This dataset provides a time resolved reference framework to distinguish time-dependent from time-independent gene regulation in HEK293T cells, informing time aware experimental design and interpretation.